Photoluminescence‐Based Characterization of Halide Perovskites for Photovoltaics. Issue 26 (6th May 2020) - Kirchartz, Thomas; Márquez, José A.; Stolterfoht, Martin; Unold, Thomas
Abstract: Photoluminescence spectroscopy is a widely applied characterization technique for semiconductor materials in general and halide perovskite solar cell materials in particular. It can give direct information on the recombination kinetics and processes as well as the internal electrochemical potential of free charge carriers in single semiconductor layers, layer stacks with transport layers, and complete solar cells. The correct evaluation and interpretation of photoluminescence requires the consideration of proper excitation conditions, calibration and application of the appropriate approximations to the rather complex theory, which includes radiative recombination, non‐radiative recombination, interface recombination, charge transfer, and photon recycling. In this article, an overview is given of the theory and application to specific halide perovskite compositions, illustrating the variables that should be considered when applying photoluminescence analysis in these materials. Abstract : Photoluminescence‐based techniques are abundantly used in the halide‐perovskite solar cell literature to study recombination in the bulk and at interfaces. This tutorial‐style progress report gives an overview over the experimental methods, the theoretical background, the current understanding, and the key open questions in the context of transient and steady‐state photoluminescence applied to perovskite solar cell materials and devices.